Controle da relação de sítios ácidos de Lewis e Brønsted pela incorporação de Sn em zeólitas Y - efeito na seletividade a produtos durante a conversão one-pot de furfural - Rodegheri, Igor (2021)
In the last years, in the production of chemicals or intermediates, the use of bioderived feedstocks as alternative sources to those derived from fossil fuels, has progressively increased. In this context, the conversion of bioderived furfural has gained much attention, through cascade reactions in a single reactor (one-pot). From this strategy, furfural can be converted in morer value-added platform molecules such as furfuryl alcohol (FA), levulinic acid (LA), angelica-lactones (AL), levulinate esters, and γ-valerolactone (GVL) through the Meerwein-Ponndorf-Verley (MPV) mechanism. In comparison with their current commercial production, which involves noble metal catalysts and high pressurized H2, this approach emerges as a greener procedure. To achieve that purpose, the MPV-catalysts must contain simultaneously Lewis (L) and Brønsted (B) acid sites. The necessary L/B acidic ratio can be adjusted in order to favour one particular reaction path to produce a desirable product. Therefore, acid zeolites can be modified to adequately fit these acid properties through the control of the B/L acidic ratio applying post synthesis treatments such as dealumination and tetravalent cations incorporation in aluminum (Al) vacancies. Among zeolites that can be applied to this objective, zeolite Y, already consolidated in industrial applications, is presented as a potential catalyst for furfural conversion. Thus, this work had the aim to prepare and modify acid Y zeolites, in a way that the B/L acidic ratio is controlled by the incorporation of tin (Sn) atoms by grafting in Al vacancies generated by steam dealumination. The zeolite Y samples were characterized by XRD, nitrogen physisorption, NH3-TPD, FTIR and DRS-UV/Vis. The furfural conversion was performed at 120 oC under atmospheric pressure during 24 h, and the yield and selectivity to products were obtained from data of GC-MS analyses. The results showed the occurrence of a gradual decrease of the B/L acidic ratio as the dealumination time was increased. After Sn grafting, the B/L ratio was modified as a function of the added Sn precursor during the treatment. Results from the furfural conversion over the studied Y zeolites showed selectivity values for the mentioned desired products lower than 5%, even at high conversion levels (>70). However, it was verified an increase of these selectivity values with a decrease of the L/B acidic ratio. Therefore, to increase the yield and selectivity to those desired products, must be applied deeper modifications, in the way to reach lower L/B acidic ratios than those obtained in this work.